Reaching the Last Mile : Social Enterprise Business Models for Inclusive Development - Tinsley, Elaine (World Bank, Washington, DC, 2018)
Bringing essential services to the poor, whether in remote rural areas, provincial towns, or in the slums of megacities, is a great challenge for governments in developing countries. Lack of governmental capacity and fiscal resources at the national and local levels prevents effective public provision of water, power, education, and health services to the poor. And private firms, which often step in to serve the middle and upper classes, are dissuaded by high risks and low affordability from providing these services to the poor, or what is sometimes referred to as “the last mile.” In contrast, social enterprises have been able to provide basic goods and services to the poor. This is the gap that the present book aims to fill. It catalogues over 40 of the most effective market-based solutions for service delivery to the poor brought about by social enterprises. It tracks how stylized business models have been developed to address development challenges. The sectors covered are education, energy, health, waste, water, sanitation, and finance. The book’s analysis employs and greatly benefits from systematically applying a common framework that helps explain the relevance and implementation of the model for even general development practitioners.